SISTEM INFORMASI RAWAT INAP PADA KLINIK HJ NINIK KUSTIANI SAMARINDA DENGAN MENGGUNAKAN MACRO MICROSOFT EXCEL - Juhairah, Rifdah; Kusumah, Angga (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2024)
This research aims to find out how to design and create a Microsoft Excel Macro application in the information system at the Hj Ninik Kustiani Samarinda Clinic. The object of this research is the Hj Clinic. Ninik Kustiani Samarinda. Data collection techniques are field studies and library research. The analysis tool used is the Microsoft Excel Macro (VBA) program command. The research results show that this application can make it easier to input data, save data, edit data, delete data, cancel data input, and print reports according to clinic needs. So the use of an Information System using Macro Microsoft Excel provides great benefits, especially in helping integrated or computerized work processes at the Hj Ninik Kustiani Samarinda Clinic.